Intervención social contra el racismo y la xenofobia - Yébenes, Jesús; Alvarez, Raquel; Alonso Ibáñez, María Rosario; Rejas, Lourdes; Alfonso, Carmen (Acciones e Investigaciones Sociales, 2011)
Intervención social contra el racismo y la xenofobia